Optimización del proceso de fumigación agrícola mediante la utilización de los drones - Navia Zamora, José Rolando (2019)
This research proposes the optimization of the processes of agricultural fumigation through the implementation of spraying drones, the purpose of this project is based on showing that by implementing this new system can encompass a greater fumigated area in a shorter time. The project was carried out in the associations of farmers registered in the Ministry of Agriculture and Livestock of Quevedo, these associations have 319 partners of which was selected a sample at random of 175 people to apply a survey where Determined how to fumigate the crops, farms were selected in which the study of methods and time to the fumigation processes used by farmers. As a result, it was obtained that 96% of the respondents carry out the fumigation of their crops by the traditional method-using a backpack-type sprinkler pump, the time of fumigated by this medium is 17, 8 hours per hectare. According to technical specifications of the drones through this system the fumigation time per hectare will be reduced to 4.5 minutes, the cost of fumigation when implementing the new fumigation system will be reduced by 48%. On the basis of feasibility of the project it is recommended that it be extended, through the Ministry of Agriculture and Livestock, to the farmers that are not part of the associations, it is suggested to make a diagnosis of the process of application of the agrochemical through the drone To verify the efficiency and efficiency of its use in relation to production, because the cost of the fumigation drones is very high it is advisable to be acquired directly by the associations and they create a fumigation department for Provide this service to your partners and other interested farmers. Keywords: Agricultural fumigation, Drones, Time study.